Cribriform prostate cancer: an aggressive pattern where definition and size matter. Issue 6 (June 2022) - Chan, Emily; Nguyen, Jane K.
Abstract: Recognition of cribriform growth pattern in prostate cancer is important for prognostic stratification and clinical decision making for many prostate cancer patients. However, as pathologists, we recognize that cribriform prostate cancer can take on many forms, and that not all morphologic variations that could potentially be considered as cribriform confer the same high–risk profile. Furthermore, a number of recent studies have shown that large cribriform glands is a more aggressive pattern and should be distinguished from small cribriform glands, though use of multiple different definitions to define size has made how to apply this distinction less clear. Here, we review the multiple patterns of cribriform architecture that one can encounter in prostate cancer and recent consensus definitions proposed for the diagnosis of cribriform prostate cancer. We highlight patterns of cribriform growth that have been shown to behave more aggressively, with a focus on size. Finally, we provide some practical considerations for reporting.